HASHTAG SEBAGAI ALAT PENYEBARAN DAKWAH DIGITAL AKUN TIKTOK @SWARGALOKA.3578 TERHADAP PROGRAM KERJA LONTONG KUPANG DALAM EDUKASI TERTIB ADMINISTRASI KEAGAMAAN - Ulfa Safira; Hafidlatul Fauzuna (Sekolah Tinggi Agama Buddha Negeri Raden Wijaya, 2026)
Hashtags (#) are metadata used in various social media today. Chris Messina was the first user on Twitter in 2007 for the news category. As social media develops, the use of hashtags has now spread to educational content, vlogs, da'wah, and government program socialization. This study discusses the use of hashtags as a new medium in digital da'wah on the TikTok platform @swargaloka.3578 as a means of educating religious administration through the